The Impact of Global Cotton and Wheat Prices on Rural Poverty in Pakistan (The Pakistan Development Review, 2006)
The incidence of rural poverty in Pakistan increased during the late 1990s after having declined during the 1980s and early 1990s. A number of structural factors have been identified as contributing to rural poverty in Pakistan. Among them are low levels of health and education spending and the unequal of farmland distribution. These structural factors help explain the levels of poverty in Pakistan, but not the increase in poverty in the late 1990s. One hypothesis is that the increase in rural poverty is the result of an adverse trend in world commodity prices, particularly cotton, a major commercial crop, and other agricultural commodities such as wheat, rice, and sugar. The overall objective of this paper is to measure the impact of changes in world commodity prices on poverty in rural Pakistan, with particular focus on cotton prices and the main cotton producing districts of Punjab and Sindh provinces.